A Millifluidic Reactor System for Multistep Continuous Synthesis of InP/ZnSeS Nanoparticles. Issue 9 (19th July 2018) - Vikram, Ajit; Kumar, Vivek; Ramesh, Utkarsh; Balakrishnan, Karthik; Oh, Nuri; Deshpande, Kishori; Ewers, Trevor; Trefonas, Peter; Shim, Moonsub; Kenis, Paul J. A.
Abstract: Despite the growing interest in quantum dots for applications ranging from bioimaging to display technologies, the reproducible and high‐quality synthesis of Cd‐free quantum dots (QDs) on a large scale remains challenging. Conventional large‐scale batch synthesis techniques are limited by slow precursor heating/cooling/mixing, poor reproducibility and low productivity. In recent years, the continuous flow synthesis of QDs using microfluidic approaches has shown promise to overcome the shortcomings of batch synthesis. However, the application of microfluidic reactors for synthesis of Cd‐free QDs exhibiting high photoluminescence quantum yield (PL QY) at high production rate remains a challenge. Here, we report a modular millifluidic reactor for the fully continuous multi‐step synthesis of InP/ZnSeS core‐shell QDs, that integrates the precise control over reaction conditions with the potential for gram‐scale production rates. We use a design of experiment approach to understand and optimize the process parameters for the synthesis, resulting in PL QY up to 67% with good reproducibility in terms of both QY and peak position (less than 5% standard deviation). Additionally, by changing the process parameters for different reaction stages (core and shell reactors), the wavelength of the InP/ZnSeS particles can be tuned to cover nearly the entire visible spectrum (480–650 nm). Abstract : In the flow : A modular and robust continuous flow reactor setup has been reported for synthesis of InP/ZnSeS nanoparticles. The process parameters are tuned to synthesize quantum dots exhibiting quantum yields as high as 67% while maintaining good reproducibility as well as high production rates on the order of 100 mg/hour using a single channelled reactor.